الحماية الجنائية للممتلكات الثقافية في مدينة القدس والقانون الدولي الإنساني - الشلالدة, محمد (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
This study aims to find out the Palestinian Antiques in the city of Jerusalem and general provisions of criminal protection for the effects according to the relevant International Conventions, also it aims to identify the criminal dimensions to protect Antiques in the city of Jerusalem. The Study clarifies the legal status of Jerusalem and International Humanitarian Law, it also addresses the scope of application of the provisions of the Scheduled protection of cultural property in Jerusalem, the study shows the International Criminal Responsibility on Israel for the crimes committed against the cultural, religious and archaeological property in Jerusalem. The study revealed the foundations and standards of criminal protection of Antiques in Jerusalem and the extent of Israel as an occupying criminal protection of the effects of commitment .